2017
DOI: 10.1016/j.jclepro.2017.08.160
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest tomato plants and urban food wastes for manufacturing plastic films

Abstract: You may download, copy and otherwise use the AAM for non-commercial purposes provided that your license is limited by the following restrictions: (1) You may use this AAM for non-commercial purposes only under the terms of the CC-BY-NC-ND license. (2) The integrity of the work and identification of the author, copyright owner, and publisher must be preserved in any copy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 20 publications
(40 reference statements)
0
16
1
Order By: Relevance
“…Along with human activities, the solid waste increment in landfills opened a Pandora's box related to the end-of-life waste management, prompting worldwide researchers to identify the best technologies for favoring waste disposal and (if possible) their recycling, aiming at environmental and economic sustainability [1][2][3][4][5][6][7]. Nowadays, significant effort has been directed toward the recovery and reuse of waste materials as new resources (based on green chemistry and circular economy guidelines) for the production of value-added products [8][9][10][11][12][13][14][15]. Among the different waste types, end-of-life waste rubber tires are one of the most voluminous wastes in terms of both shape and quantity (the European consumption of tires is about 3.2 million tons per year) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Along with human activities, the solid waste increment in landfills opened a Pandora's box related to the end-of-life waste management, prompting worldwide researchers to identify the best technologies for favoring waste disposal and (if possible) their recycling, aiming at environmental and economic sustainability [1][2][3][4][5][6][7]. Nowadays, significant effort has been directed toward the recovery and reuse of waste materials as new resources (based on green chemistry and circular economy guidelines) for the production of value-added products [8][9][10][11][12][13][14][15]. Among the different waste types, end-of-life waste rubber tires are one of the most voluminous wastes in terms of both shape and quantity (the European consumption of tires is about 3.2 million tons per year) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, poly(vinyl alcohol‐ethylene) was combined with 20 to 100 g kg −1 post‐harvest tomato (plant powder) and processed by a single extrusion screw for the manufacture of plastic films. It was concluded that these films are a good option when compared to other commercial materials because of cost‐effectiveness . Hemicellulose films of sugarcane bagasse extracted by alkaline hydrolysis and produced by the casting technique show good potential for the production of biodegradable films …”
Section: Plastics In the Agricultural Sector And Biodegradable Materialsmentioning
confidence: 99%
“…It was concluded that these films are a good option when compared to other commercial materials because of cost-effectiveness. 24 Hemicellulose films of sugarcane bagasse extracted by alkaline hydrolysis and produced by the casting technique show good potential for the production of biodegradable films. 25 Biopolymers, regardless of their application, must meet certain requirements, such as good barrier properties (water, gas, and oil), good mechanical properties (resistance, stress-resistance, elasticity) and good visual properties (translucence, lack of color).…”
Section: Plastics In the Agricultural Sector And Biodegradable Materialsmentioning
confidence: 99%
“…The exploitation of renewable resources as an alternative feedstock for the production of value-added bio-based chemicals and materials has dramatically increased in recent decades [1][2][3][4][5][6][7][8][9][10]. Among the different substrates, the use of an organic fraction from urban and/or agricultural waste has attracted the attention of experts driven by the principles of a circular (and sustainable) economy ( [11,12] and references therein).…”
Section: Introductionmentioning
confidence: 99%